2010
DOI: 10.1016/j.placenta.2010.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Matrix Association: Switching to the Invasive Cytotrophoblast

Abstract: Abnormal trophoblast invasion is associated with the most common and most severe complications of human pregnancy. The biology of invasion, as well as the etiology of abnormal invasion remains poorly understood. The aim of this study was to characterize the transcriptome of the HTR-8/SVneo human cytotrophoblast cell line which displays well characterized invasive and non-invasive behavior, and to correlate the activity of the transcriptome with nuclear matrix attachment and cell phenotype. Comparison of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…These have including the development of unique genomic array system capable of simultaneously and specifically assaying the single copy transgenic human protamine domain in addition to the endogenous locus (Johnson G.D. 2010). Utilizing these methods similar studies have been reported in varied somatic cell-types (Linnemann et al 2007, Linnemann & Krawetz 2009, Linnemann et al 2009, Drennan et al 2010). Preliminary analysis of the human sperm nuclear matrix from four donors has yielded intriguing results (Figure 2A and B).…”
Section: The Sperm Nuclear Matrixmentioning
confidence: 64%
See 2 more Smart Citations
“…These have including the development of unique genomic array system capable of simultaneously and specifically assaying the single copy transgenic human protamine domain in addition to the endogenous locus (Johnson G.D. 2010). Utilizing these methods similar studies have been reported in varied somatic cell-types (Linnemann et al 2007, Linnemann & Krawetz 2009, Linnemann et al 2009, Drennan et al 2010). Preliminary analysis of the human sperm nuclear matrix from four donors has yielded intriguing results (Figure 2A and B).…”
Section: The Sperm Nuclear Matrixmentioning
confidence: 64%
“…The strong fluorescent signal corresponds to chromatin at the bases of the DNA loop domains which remain associated with the nuclear matrix (Kramer & Krawetz 1996). Similar extraction protocols are commonly used with somatic cells; though due to the absence of disulfide bonds reducing agents are not required (Berezney & Coffey 1977, Linnemann et al 2009, Drennan et al 2010). …”
Section: The Sperm Nuclear Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, we also observed that nGPx4 has a specific subnuclear distribution in the nuclear matrix of haploid male germ cells, from round spermatids to cauda epididymal sperm 12 . Although the reason for this localization remains unclear, it is indeed intriguing, because nuclear matrix binds chromatin at sequence-specific regions of attachment, the so-called matrix attachment regions (MARs), which exhibit a variety of functions, including chromosome organization into discrete domains and chromatin potentiation 14 , 15 . As an example, the sperm genome displays two haploid-specific MARs flanking the protamine domain, a DNA region containing a cluster of three genes encoding the proteins responsible for DNA packaging protamine 1, protamine 2, and transition protein 2 16 , 17 .…”
Section: Introductionmentioning
confidence: 82%
“…S/MARs anchor chromatin onto the NM, thereby organizing the genomic DNA into topologically distinct loop domains that are important for the regulation of replication and transcription. 2 Despite numerous genomic studies, [3][4][5][6][7] no consensus S/MAR sequence has been identified so far. 8 S/MARs can be both A/T 9 or G/C rich.…”
Section: Introductionmentioning
confidence: 99%